Caregiving experiences among parents of children with physical and intellectual disabilities: a qualitative systematic review - Mundakir, Mundakir; Choliq, Idham; Sukadiono, Sukadiono; Fitriyani, Vika Ramadhana; Firman, Firman (Jurnal Ners, 2024)
Introduction: This study aimed to identify caregiver experiences encountered by parents of children with physical and intellectual disabilities. Methods: The study used a systematic review method with the guidelines of Enhancing Transparency in Reporting the Synthesis of Qualitative Research (ENTREQ) and PRISMA 2020. The review focused on parents caring for children with physical and intellectual disabilities. The literature was searched for relevant studies from five electronic databases including PubMed, CINAHL, Web of Science (core collection), Cochrane, and Scopus. This systematic review examined 14 articles out of a total of 63,400 articles found. The study used a thematic analysis method to analyze the study. Results: Providing care for children with physical and intellectual disabilities requires addressing a variety of challenges. It is critical to have a comprehensive understanding of these intricacies to ensure that families receive the necessary support and interventions. Our synthesis identified seven themes: (1) gendered and emotional experiences, (2) compromising quality of life: physical and psychological impact, (3) lack of knowledge about disabilities, (4) lack of social support, (5) stigma, (6) uncertain future of the recipient, and (7) unavoidable caregiving responsibility. Conclusions: The results of this study provide recommendations that health professionals and researchers further explore these challenges and strive to build a supportive and inclusive environment that recognizes the unwavering dedication of parents and prioritizes the optimal care and development of children with disabilities. Keywords: children, disability, parent, qualitative systematic review